Marshes of Southern Iraq and Some Economic Activities of its inhabitants. (Journal of Misan Researches, 2024)
This study aims to explain an important conception of the marshland region in southern Iraq from two important aspects. The first is to explain natural geographical characteristics of the marshland areas in terms of the way they are formed. It has also been shown that there are distinct climatic characteristics of marshes areas in terms of temperature, evaporation, relative humidity and rain that may be relatively different from that prevailing in other sedimentary plain areas in Iraq. The study also demonstrated the paramount importance of the marshland's water recharge sources, which included the sprawling streams of the Tigris and Euphrates rivers, as well as watercourses hailing from the Iranian highlands from the east. The second aspect of this study focused on two importance activity carried out by the inhabitants of the southern Iraqi lagoons: bird hunting and fishing, which clearly showed that the natural environment contributed to the requirements of these crafts in the region. The diversity of birds and fish caused the diversity of their fishing methods, which the population is keen to follow strictly